2010
DOI: 10.1111/j.1742-7843.2010.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐Regulation of G‐Protein‐Coupled Receptors for Endothelin and Thromboxane by Lipid‐Soluble Smoke Particles in Renal Artery of Rat

Abstract: Up-regulation of G-protein-coupled receptors (GPCR) plays key roles in renal hypertension and cardiovascular disease pathogenesis. The present study was designed to examine if lipid-soluble cigarette smoking particles (DSP), nicotine and endotoxin (LPS), induce GPCR up-regulation for thromboxane A 2 (TP), endothelin type A (ET A ) and type B (ET B ) receptors in renal artery, and if intracellular signal mechanisms are involved. Renal artery segments of rats were exposed to DSP, nicotine or LPS, in organ cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Increased renal artery contractility leads to increased renal vascular resistance and reduced renal blood flow, which is often seen in renal vasospasm , renal artery stenosis and endotoxaemic shock‐induced renal ischaemia . Previously, we have reported that rat renal artery segments exposed to smoke particles increase renal artery contractility through transcriptional and post‐transcriptional up‐regulation of contractile GPCRs for endothelin and thromboxane . The present study has demonstrated that organ culture of renal artery segments increases renal artery contractility via up‐regulation of both ET A and ET B2 receptors in the smooth muscle cells.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Increased renal artery contractility leads to increased renal vascular resistance and reduced renal blood flow, which is often seen in renal vasospasm , renal artery stenosis and endotoxaemic shock‐induced renal ischaemia . Previously, we have reported that rat renal artery segments exposed to smoke particles increase renal artery contractility through transcriptional and post‐transcriptional up‐regulation of contractile GPCRs for endothelin and thromboxane . The present study has demonstrated that organ culture of renal artery segments increases renal artery contractility via up‐regulation of both ET A and ET B2 receptors in the smooth muscle cells.…”
Section: Discussionsupporting
confidence: 50%
“…Previously, we have studied the effects of dimethylsulphoxide (DMSO)‐extracted smoke particles (DSP) on rat renal artery contractility. The results show that DSP transcriptionally up‐regulates ET B2 receptors with enhanced contraction in rat renal artery, whereas up‐regulation of ET A and thromboxane receptor‐mediated contraction may involve post‐transcriptional mechanisms . The present study demonstrates that organ culture induces increased renal artery contractility through transcriptional up‐regulation of both ET A and ET B2 receptors in the smooth muscle cells, and activation of NF‐κB‐mediated transcriptional mechanisms is involved in this process.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Landmark papers [2], [3] have demonstrated that COX-derived prostanoids (prostacyclin and thromboxane) significantly influence cardiovascular disease, with thromboxane promoting atherothrombotic events. Diabetes mellitus [4] , [5], smoking [6], [7], [8], and obesity [9], [10] (key cardiovascular risk factors) are associated with increased thromboxane levels. Low dose aspirin, a cyclooxygenase inhibitor (COX-1>> COX-2), reduces platelet thromboxane production leading to protective effects in women (against strokes) and men (myocardial events) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-soluble smoke particles consisting of DMSO-soluble particles (DSP), nicotine, and lipopolysaccharides, upregulate G protein-coupled receptors for potent contractile agents, endothelin and thromboxane, [128] which contribute to endothelial dysfunction [129]. In addition to upregulating contractile receptors, LPS exposure simultaneously increases activation of inflammatory and contractile thromboxane and angiotensin I receptors while inhibiting anti-inflammatory and dilatory prostacyclin and acetylcholine receptors [130].…”
Section: Smoking and Oxidative Stressmentioning
confidence: 99%